2015
DOI: 10.1038/ncomms8490
|View full text |Cite
|
Sign up to set email alerts
|

PPL2ab neurons restore sexual responses in aged Drosophila males through dopamine

Abstract: Male sexual desire typically declines with ageing. However, our understanding of the neurobiological basis for this phenomenon is limited by our knowledge of the brain circuitry and neuronal pathways controlling male sexual desire. A number of studies across species suggest that dopamine (DA) affects sexual desire. Here we use genetic tools and behavioural assays to identify a novel subset of DA neurons that regulate age-associated male courtship activity in Drosophila. We find that increasing DA levels in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…Nor were SMPa fluorescence changes observed in the calciuminsensitive fluorescent protein tdTomato (p > 0.95) or with immunostaining of fixed TH > GCaMP6s brains (p > 0.92) ( Figures S7A and S7B). The mating-history-dependent GCaMP6s fluorescence change in SMPa was also detected using VT02857-Gal4, which labels aSP4 and a few other dopaminergic neurons ( Figure 6D) (Keleman et al, 2012;Yu et al, 2010), as well as NP5945-Gal4, which labels neurons in four dopaminergic clusters ( Figures 6E and 3I) (Kuo et al, 2015). These results show that dopaminergic activity in the vicinity of the connection to P1 neurons serves as a neuronal correlate of male mating drive.…”
Section: Dopaminergic Activity In the Smpa Is A Neuronal Correlate Ofmentioning
confidence: 58%
See 1 more Smart Citation
“…Nor were SMPa fluorescence changes observed in the calciuminsensitive fluorescent protein tdTomato (p > 0.95) or with immunostaining of fixed TH > GCaMP6s brains (p > 0.92) ( Figures S7A and S7B). The mating-history-dependent GCaMP6s fluorescence change in SMPa was also detected using VT02857-Gal4, which labels aSP4 and a few other dopaminergic neurons ( Figure 6D) (Keleman et al, 2012;Yu et al, 2010), as well as NP5945-Gal4, which labels neurons in four dopaminergic clusters ( Figures 6E and 3I) (Kuo et al, 2015). These results show that dopaminergic activity in the vicinity of the connection to P1 neurons serves as a neuronal correlate of male mating drive.…”
Section: Dopaminergic Activity In the Smpa Is A Neuronal Correlate Ofmentioning
confidence: 58%
“…We therefore screened $30 Gal4 lines labeling dopaminergic neurons, looking for lines that could overcome satiety when activated together with aSP4. We identified NP5945-Gal4 (Kuo et al, 2015), which does not label aSP4 and did not reverse satiety when stimulated alone, but did increase mating behavior from satiated males when stimulated together with VT02857 ( Figure 3G). Silencing either VT02857 or NP5945 neurons in adults using Kir2.1 decreased courtship behavior ( Figure 3H), suggesting that the combined activity of these two neuronal populations is necessary to promote the normal accrual of mating drive.…”
Section: Figure 2 Mating Drive Reflects But Is Not Acutely Instructmentioning
confidence: 99%
“…To study PPL2ab neurons genetically, we first confirmed that DAergic PPL2ab neurons can be targeted using different PPL2ab expression drivers ( murashka-1-Gal4, NP5945-Gal4, NP3024-Gal4 , and LG121-LexA ) by performing TH immunostaining (Fig. 1a–d)2. We then selectively overexpressed TH in PPL2ab neurons by placing the UAS-TH transgene under the control of different PPL2ab-specific expression drivers ( murashka-1-Gal4  >  UAS-TH, NP5945-Gal4  >  UAS-TH, NP3024-Gal4  >  UAS-TH , and LG121-LexA  >  LexAop-TH ).…”
Section: Resultsmentioning
confidence: 94%
“…In the past several years, advances in genetic and imaging tools have allowed remarkable progress in identifying the modulatory neural circuits for experience‐ and age‐dependent changes in mating drive (Kuo et al . ; Zhang et al . ).…”
mentioning
confidence: 99%
“…Aged males on the other hand have declined sexual drive, which is due to a decreased dopamine level in the PPL2ab neurons (Kuo et al . ) although the receptor mediating this activity is unknown.…”
mentioning
confidence: 99%